Nadwah Usbu’iyyah as A Pedagogical Framework for Enhancing Students’ Mastery of Arabic Grammar - Mawardi Mawardi; Annisa Zahra Jabbar; Firman Firman; Hasriadi Hasriadi (Journal of Educational Studies, 2026)
Arabic language learning among students of the Arabic Language Education Program at UIN Palopo often faces challenges, particularly in mastering grammatical rules. This study aims to investigate the effect of the Nadwah Usbu’iyyah program on students’ Arabic grammar proficiency. Using a quantitative approach, data were collected through observation, interviews, and pretest and posttest instruments. The sample consisted of 19 students from the Arabic Language Education Department who actively participated in the Nadwah Usbu’iyyah program. The results revealed a significant difference between pre-test and post-test scores, with a calculated t-value of 11.25, which exceeds the critical value of 1.734. This indicates that the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected. Furthermore, the average post-test score (78) was higher than the pre-test score (61), demonstrating a notable improvement. These findings suggest that the Nadwah Usbu’iyyah program has a significant positive effect on enhancing students’ mastery of Arabic grammar. Therefore, it is recommended as an effective supplementary learning strategy in Islamic higher education institutions.